P‐4.6: Efficient Synthetic Encoding Algorithm based on Depth Offset Mapping for Tabletop Integral Imaging Display - Wang, Peiren; Wang, Yong; Nie, Wei; Li, Zhengyang; Li, Zilong; Han, Xue (SID International Symposium Digest of technical papers, 2023)
An efficient algorithm of three‐dimensional image rendering based on depth offset mapping for tabletop integral imaging display system is proposed. The two‐dimensional color image is used as the reference image, and the corresponding gray depth image is used to obtain the depth information. The offset of pixels in each elemental image array is calculated along the horizontal and vertical directions. According to the geometric relationship between the integral imaging display panel and the viewing position, the synthesized three‐dimensional image can be rendered directly. Compared with the traditional method based on virtual viewpoints generation, the proposed algorithm has fast computational speed and high rendering efficiency. The effectiveness of this method is verified by experiment, which can provide high quality three‐dimensional display effect.